A critical appraisal of the principal guidelines for neurogenic lower urinary tract dysfunction using the AGREE II instrument. Issue 8 (30th July 2018) - Jaggi, Ashley; Drake, Marcus; Siddiqui, Emad; Nazir, Jameel; Giagos, Vasileios; Fatoye, Francis
Abstract : Aims: The process of identifying research questions, synthesizing and interpreting evidence, and weight given to health economics differs between the clinical guidelines (CGs) for neurogenic lower urinary tract dysfunction (NLUTD). Consequently, the quality also varies which can have implications for clinical practice. Methods: We used the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument to assess the quality of the National Institute for Health and Care Excellent (NICE), European Association of Urology (EAU), and the International Consultations on Incontinence (ICI) CGs on neurogenic bladder. Results: The NICE CGs were deemed to be of the highest quality (overall score of 92%). NICE were the only guidelines to systematically incorporate cost‐effectiveness research into their recommendations. The EAU CGs received an overall score of 83% and the ICI CGs achieved the lowest overall score (75%). The highest scoring domain among all the CGs was scope purpose (86%) and the lowest scoring domain was applicability (69%). All guidelines were recommended for use (mostly with some modifications). Conclusions: All CGs had their inherent advantages and disadvantages, though all were still deemed to be of high quality. Incorporating cost‐effectiveness research would be near impossible for guidelines with a broad‐country remit. Incorporating the AGREE II instrument in the development of CGs and better collaboration between the ICI, NICE, and EAU could improve the quality, and consistency between NLUTD CGs and ultimately improve health outcomes for this important patient group.